HARTA PENINGGALAN DARI PEWARIS TERHADAP HAK WARIS ANAK PEREMPUAN DI BALI - Rafiqi, Rafiqi (Jurnal Ilmiah Penegakan Hukum, 2014)
In Indonesia get law cultures, but in In donesia do not law, because in Indonesiafamous Kitab undang- Undang Hukum Perdata Burgerlijke Wetboek).In case getin Bali, women can leegaty same with man. Progress development law culturegovermen to do law indivudulais.